2014
DOI: 10.1152/ajpregu.00082.2014
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant low-dose doxorubicin treatment and exercise

Abstract: Cardiotoxicity is a side effect for cancer patients treated with doxorubicin (DOX). We tested the hypothesis that low-intensity aerobic exercise concomitant with DOX treatment would offset DOX-induced cardiotoxicity while also improving the therapeutic efficacy of DOX on tumor progression. B16F10 melanoma cells (3 ϫ 10 5 ) were injected subcutaneously into the scruff of 6-to 8-wk-old male C57BL/6 mice (n ϭ 48). A 4 mg/kg cumulative dose of DOX was administered over 2 wk, and exercise (EX) consisted of treadmil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 35 publications
3
52
0
2
Order By: Relevance
“…Similar findings have been reported in experimental studies with animals showing myocyte atrophy (46) to be related to LV mass reduction during anthracycline treatment.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings have been reported in experimental studies with animals showing myocyte atrophy (46) to be related to LV mass reduction during anthracycline treatment.…”
Section: Resultssupporting
confidence: 89%
“…Recent experimental studies demonstrated that early and subclinical myocardial effects of AIC included increased levels of interstitial fibrosis, edema, and reduced cardiomyocyte size (46), which may all be potentially characterized by cardiac magnetic resonance (CMR).…”
mentioning
confidence: 99%
“…The use of DOX is limited for chemotherapy due to its toxicity (26,27). It disrupts the oxidant-antioxidant systems, resulting in tissue damage caused by lipid peroxidation and protein oxidation (28). The present study revealed severe biochemical changes as well as an oxidative damage in cardiac tissue after treatment with 20mg.kg -1 of DOX.…”
Section: / Hashemi Chashmi and Colleaguesmentioning
confidence: 52%
“…Regular exercise improves metabolism and especially mitochondrial capacity in the hearts of former Doxo patients. A study showed that low-intensity aerobic exercise, concomitant with low-dose Doxo administration (cumulative dose of 4mg/kg) would mitigate the Doxo-induced cardiotoxicity while also improving the therapeutic efficacy of Doxo in a murine model of melanoma [138]. Exercise training protects against Doxoinduced myopathy in both heart and skeletal muscles, by reducing FoxO1 and FoxO3 expression, and the transcription of their target genes [i.e., atrogin-1/muscle atrophy F-box (MaFbx), muscle ring finger-1 (MuRF-1), and BCL2/adenovirus E1B 19 kDa proteininteracting protein 3 (BNIP3)].…”
Section: Physical Activity As a Possible Alternative Strategy For Prementioning
confidence: 99%